2004
DOI: 10.1124/jpet.104.076547
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate (mGLU)2/3 Receptor Antagonist LY341495 [2S-2-Amino-2-(1S,2S-2-carboxycyclopropyl-1-yl)-3-(xanth-9-yl)propanoic Acid] Stimulates Waking and Fast Electroencephalogram Power and Blocks the Effects of the mGLU2/3 Receptor Agonist LY379268 [(-)-2-Oxa-4-aminobicyclo[3.1.0]hexane-4,6-dicarboxylate] in Rats

Abstract: The highly selective metabotropic glutamate (mGlu)2/3 receptor agonist LY379268 [(Ϫ)-2-oxa-4-aminobicyclo[3.1.0]hexane-4,6-dicarboxylate] completely suppresses rapid eye movement (REM) sleep and strongly depresses theta (6 -10 Hz) and high-frequency (10 -60 Hz) power in the waking and nonrapid eye movement (NREM) EEG, effects consistent with depressed brain excitation (arousal). We hypothesized the selective mGlu2/3 receptor antagonist LY341495 [2S-2-amino-2-(1S,2S-2-carboxycyclopropyl-1-yl)-3-(xanth-9-yl)prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 13 publications
5
18
0
Order By: Relevance
“…Interestingly, it has also been shown that MGS0039 enhanced social recognition memory in rats, which was dependent on AMPA receptor activation (Shimazaki et al, 2007) and attenuated the learning deficit in a passive avoidance test induced in rats by olfactory bulbectomy (Palucha-Poniewiera et al, 2010). It has also been shown that LY341495 exhibits mild arousal enhancing effects in rats (Feinberg et al, 2005). Subsequently, it has been proposed that mGlu2/3 receptor antagonists may have an antidepressant profile with wakepromoting and cognition enhancing effects (Witkin and Eiler, 2006).…”
Section: Mglu2/3 Nam Increases Ltp Following Theta Burst Stimulation mentioning
confidence: 94%
“…Interestingly, it has also been shown that MGS0039 enhanced social recognition memory in rats, which was dependent on AMPA receptor activation (Shimazaki et al, 2007) and attenuated the learning deficit in a passive avoidance test induced in rats by olfactory bulbectomy (Palucha-Poniewiera et al, 2010). It has also been shown that LY341495 exhibits mild arousal enhancing effects in rats (Feinberg et al, 2005). Subsequently, it has been proposed that mGlu2/3 receptor antagonists may have an antidepressant profile with wakepromoting and cognition enhancing effects (Witkin and Eiler, 2006).…”
Section: Mglu2/3 Nam Increases Ltp Following Theta Burst Stimulation mentioning
confidence: 94%
“…An additional test in four monkeys determined the effects of 10.0 mg/kg LY341495 on cocaine self-administration in the absence of LY379268. The dose of LY341495 was selected on the basis of a previous report demonstrating central activity and antagonism of the effects of LY379268 in rodents (Feinberg et al, 2005) and on preliminary observations that the dose was well tolerated in squirrel monkeys.…”
Section: Group II Mglur Agonist and Cocaine In Monkeysmentioning
confidence: 99%
“…LY379268 has been found to reduce locomotor activity, rapid eye movement sleep, and fast (10 -50 Hz) electroencephalographic wave recordings in rats, leading to speculation that the drug acts as a functional depressant of central arousal systems (Feinberg et al, 2002(Feinberg et al, , 2005. Observational studies in squirrel monkeys, however, revealed no significant effect of LY379268 on locomotor activity, resting posture, or other behaviors that might reflect reduced arousal.…”
Section: Group II Mglur Agonist and Cocaine In Monkeys 929mentioning
confidence: 99%
“…Based upon these data, it was hypothesized that LY341495 would have the opposite effects of the mGlu2/3 receptor agonist. Indeed, LY341495 increased waking and waking EEG by reducing nREM and REM sleep [Feinberg et al, 2005]. LY341495 also depressed lowfrequency and stimulated high-frequency EEG power.…”
Section: Daytime Sleepinessmentioning
confidence: 98%
“…LY341495 has electroencephalogram (EEG) activating effects in rats [Feinberg et al, 2005], and Feinberg et al [2002] have found opposing EEG suppressant effects of the mGlu2/3 agonist LY379268. Indeed, the effects of LY341495 can be prevented by LY379268.…”
Section: Mood Disordersmentioning
confidence: 99%